A colorimetric and fluorescence turn-on probe for the detection of ascorbic acid in living cells and beverages. (30th November 2021) - Wu, Aimin; Ding, Hao; Zhang, Wei; Rao, Hanbing; Wang, Lizhi; Chen, Yinyin; Lu, Changfang; Wang, Xianxiang
Highlights: A colorimetric and fluorescence turn-on dual-signal method for the detection of ascorbic acid was developed. The established probe was used successfully for ascorbic acid detection in living cells and beverages. A linear detection range for ascorbic acid is 1–200 μM and the LOD is 0.15 µM and 0.023 µM by fluorescence method and colorimetric, respectively. Abstract: A colorimetric and fluorescence turn-on dual-signal assay was developed for the determination of ascorbic acid (AA). Because the ultraviolet absorption of the oxidized 3, 3′, 5, 5′-tetramethylbenzidine (oxTMB) overlapped with the fluorescence emission of glutathione stabilized Au nanoclusters (AuNCs), the fluorescence of AuNCs can be quenched by oxTMB. When AA was added, the blue oxTMB was reduced to colorless TMB, and the fluorescence of AuNCs was restored simultaneously. The decrease in absorbance and increase in fluorescence signal depended on the concentration of AA. In the determination range of 0.5 to 200 μM, the detection limits (LOD) for AA were as low as 0.15 µM and 0.22 µM for fluorometric and colorimetric, respectively. The established probe was used successfully for AA detection in living cells and beverages.